1995
DOI: 10.1159/000188578
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lp(a) Concentrations and Some Potential Effects in Hemodialysis, CAPD, Transplantation, and Control Groups, and Review of the Literature

Abstract: Apolipoprotein (a) – Lp(a) – is reported to be an independent risk factor for coronary artery disease and for hemodialysis (HD) access occlusion. Homology with plasminogen may predispose to thrombosis. High concentrations usually have been reported in patients on HD and on continuous ambulatory peritoneal dialysis (CAPD), but near-normal values in many kidney transplants (TP). We used Pharmacia immunoradiometric assay in 52 patients on HD, 58 on CAPD, 94 after TP, and 56 controls. The Lp(a) mean levels for CAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 51 publications
3
14
0
1
Order By: Relevance
“…In our study, Lp(a) concentrations were not influenced by short-term fluvastatin therapy. It has been observed that both sinivastatin and lovastatin also did not alter Lp(a) levels in kidney allograft recipients [28].…”
Section: Discussionmentioning
confidence: 98%
“…In our study, Lp(a) concentrations were not influenced by short-term fluvastatin therapy. It has been observed that both sinivastatin and lovastatin also did not alter Lp(a) levels in kidney allograft recipients [28].…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, mixed results regarding Lp(a) have been reported from cross sectional studies (163,169,174,185,(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204). Notably, the decrease of Lp(a) in renal transplant patients was in dependent of the modality of immunosuppressive therapy (169,(184)(185)(186)(187)(188)(189)(190)(191), arguing against a contribution by an in flammatory component.…”
Section: Menopausementioning
confidence: 99%
“…The influence of renal transplantation on Lp(a) con centrations has also been investigated and prospective studies generally demonstrate a decrease of Lp(a) levels following kidney transplantation (169,(184)(185)(186)(187)(188)(189)(190)(191)(192)(193), although the followup period has been limited. In contrast, mixed results regarding Lp(a) have been reported from cross sectional studies (163,169,174,185,(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204).…”
Section: Menopausementioning
confidence: 99%
See 1 more Smart Citation
“…Even though predialysis patients exhibit high serum Lp(a) levels [5, 6], there are sparse data with regard to serum Lp(a) concentrations in patients with mild/moderate renal failure [7, 8]. …”
Section: Introductionmentioning
confidence: 99%